Optimalisasi Arsitektur Tajuk dan Iklim Mikro melalui Transfer Teknologi Pemangkasan Kakao di Nagari Sitiung - Siska Efendi; Adrinal Adrinal; Ade Noferta; Dewi Rezki; Yulistriani Yulistriani; Wulan Kumala Sari (Buletin Dharmas Andalas, 2026)
Low cocoa productivity in Dharmasraya Regency, reaching only 549.94 kg/ha , is closely related to limited farmer knowledge regarding standard canopy management. This community service activity aims to optimize canopy architecture and improve the garden's microclimate through pruning technology transfer for farmers in Nagari Sitiung. The activity was implemented using module-assisted counseling and field training by creating demonstration plots (demplot) for Immature Plants and Mature Plants. The results showed an increase in the technical understanding and skills of the partner farmer groups regarding four main types of pruning: shape, maintenance, production, and restoration pruning. Through proper canopy management, the Leaf Area Index (LAI) value can be optimized and garden humidity can be controlled to reduce the risk of pest and disease attacks. It can be concluded that this technology transfer has succeeded in improving farmers' competence in managing cocoa plant canopy architecture as an effort to increase productivity sustainably. As a follow-up, it is recommended to provide continuous assistance regarding side-grafting techniques to rehabilitate unproductive plants.